TEACHERS' TRAINING FOR SOCIAL AND EDUCATIONAL ACTIVITY IN CONDITIONS OF MOUNTAIN AREA PRIMARY SCHOOL - Olena Budnyk (Vasyl Stefanyk Precarpathian National University, 2015)
The article highlights the keynotes of professional training of elementary school teacher to social and pedagogical activity with pupils and their parents taking into consideration specific character of mountain landscape-climatic and ethnocultural environment. Author focuses on engaging students of teacher training institutions in research work according to outlined problems, the creation of individual database on cultural issues, enhance their performance by varied forms and methods of teaching in the humanities. The author stresses the importance of independent ethnographic activity of future teachers, in particular the study of crafts and trades of mountainous region, the folklore and customs of the locals, collecting vintage household items and their local historical analysis. Ideological value orientations of the inhabitants of the mountains is a key component of spiritual values and the basic formation of the structure of consciousness and awareness of the growing personality. Deeper knowledge of students priority of moral, aesthetic, civic values of people from mountain terrain and features of the landscape, climate, flora and fauna of mountain environment will help them develop their future careers, which is to foster harmonious child in primary school environment.